PENERAPAN METODE AL-‘ARABIYYAH BAYNA YADAIKA’ DALAM PEMBELAJARAN BAHASA ARAB DI MA’HAD AL-BIRR MAKASSAR - Muchtar, Muhammad Ilham (State Institute of Islamic Studies (IAIN) Palu, 2015)
This study aims to determine the method of teaching Arabic language proficiency by using a guide book Al-'Arabiyyah Bayna Yadaik and uncover its effectiveness in improving student proficiency in Arabic for the students of Ma'had Al-Birr Makassar. This research based field (field research ) because the data obtained from the respondents and informants more use of techniques and methods of field collection data. Respondents involved in this study were 50 students who were randomly selected by the criteria that had been predetermined. The results showed that the book Al-'Arabiyyah bayna Yadaik quite effective in increasing student mastery of Arabic language proficiency at Ma'had Al-Birr Makassar, as demonstrated by the results of tests conducted on respondents.